DEVELOPMENT OF EVALUATION INSTRUMENTS BASED ON GOOGLE FORMS FOR GRADE IV ELEMENTARY SCHOOL ON THE FORCE TOPIC - Qomar, Mohamad Nurul; Utaminingsih, Esty Setyo (Research and Development Journal of Education, 2025)
Evaluation is necessary in education to determine the effectiveness of the educational process in relation to students. Seeing that most educational evaluation systems in elementary schools still use the classical mode, they are less relevant and practical, there is a need for educational evaluation innovation. In this case, the use of Google Forms as an educational evaluation tool. This research aims to develop a Google Form-based evaluation instrument to improve the learning outcomes of style materials. Validity testing of the Google Forms–based evaluation instrument yielded 0.96 for content validity, 0.88 for construct validity, and 0.97 for language validity. The final validity index was 0.936, classified as excellent and relevant. The Google Form–based evaluation instrument was feasible for improving the learning outcomes of fourth-grade students on the ‘Style’ material in elementary school.